2011
DOI: 10.1002/masy.201100032
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hydrogels by Enzymatic Co‐Crosslinking of Dextran and Hyaluronic Acid Tyramine Conjugates

Abstract: In this study, injectable hydrogels were prepared by the horseradish peroxidase mediated co‐crosslinking of dextran‐tyramine (Dex‐TA) and hyaluronic acid‐tyramine (HA‐TA) conjugates intended for cartilage tissue engineering. In general the gelation times of 10 wt% polysaccharide solutions are < 20 seconds and their storage moduli can be adjusted by varying the composition between Dex‐TA and HA‐TA. Dex‐TA/HA‐TA (50/50) hydrogels were fully degradable in the presence of hyaluronidase. Chondrocytes incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Previously, we have shown that Dex‐TA gels very slowly degrade, which may hamper cartilage tissue regeneration. Combining Dex‐TA with HA‐TA at a 50/50 weight ratio resulted in a hydrogel, which degraded in approximately 50 days . It was also shown that the ultimate stress and ultimate strain, as determined by rheology, even exceed that of a Dex‐TA hydrogel at a similar concentration.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Previously, we have shown that Dex‐TA gels very slowly degrade, which may hamper cartilage tissue regeneration. Combining Dex‐TA with HA‐TA at a 50/50 weight ratio resulted in a hydrogel, which degraded in approximately 50 days . It was also shown that the ultimate stress and ultimate strain, as determined by rheology, even exceed that of a Dex‐TA hydrogel at a similar concentration.…”
Section: Resultsmentioning
confidence: 97%
“…Phosphate buffered saline (PBS, pH 7,4) was purchased from B. Braun Co. The Dex‐TA conjugate and HA‐TA conjugate were synthesized using slightly modified procedures as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This also applies tyrosinase, phosphopantetheinyl transferase, lysyl oxidase, plasma amine oxidase, and phosphatases [498]. It made it possible in particular to develop new gels by engrafting tyramine groups into natural and synthetic polymers such as dextran, hyaluronic acid, alginate, cellulose, gelatin, heparin and PEG-PPO [499][500][501][502][503][504][505]509].…”
Section: Selection Of Technologies Of Implantable Devices In Regeneramentioning
confidence: 99%